Uma abordagem para um ambiente pervasivo voltado ao cuidado de pacientes com demência em ambientes de homecare - Bastiani, Ederson (2013)
The increasing number of eldery people is demanding increasingly infrastructure of health systems mainly due to the incidence of diseases associated with older profile. Among these, one of the most worrying is dementia, a syndrome that progressively affects cognitive and motor functions of patients, who become dependent care and constant monitoring. The home care could mean an interesting alternative to avoid a possible hospitalar collapse , providing care to patients in their own home. However, the home environment can become complex, since often the caregiver is someone of the family and does not have the correct technique of monitoring or being inattentive due to wear caused by intense patient care. Thus it becomes necessary to develop solutions which reduce the overhead of the caregiver while the patient continues to be monitored. One way to achieve such solutions is by applying concepts of pervasive computing in home environments. Through an environment populated by sensors and other computing devices the patient can be monitored constantly and the environment can adapt to the needs of the user, anticipating the situations according to the current context. For this, the context must be represented clearly and with the semantics of their entities well-defined. Considering this, this work presents a approach for pervasive environments aimed to the care of the patients with dementia in homecare environments. This approach is composed of an architecture for development of pervasive systems, and an ontology for knowledge representation environments pervasive oriented to patients with this profile. It is believed, with the approach proposed, preserve the autonomy of patients as well as stimulate their cognitive functions remaining, besides to reduce the burden suffered by their caregivers.